A Novel Ferroptosis-Related Pathway for Regulating Immune Checkpoints in Clear Cell Renal Cell Carcinoma - Gao, Su; Ruan, Hailong; Liu, Jingchong; Liu, Yuenan; Liu, Di; Tong, Junwei; Shi, Jian; Yang, Hongmei; Xu, Tianbo; Zhang, Xiaoping (Frontiers in Oncology, 2021)
Ferroptosis is a novel form of cell death and plays a role in various diseases, especially tumours. It has been reported that ferroptosis is involved in the growth and progression of clear cell renal cell carcinoma (ccRCC); however, the specific molecular mechanisms are still unclear. In this study, we constructed a 4-gene signature (FeSig) of ferroptosis-related genes via Cox regression analysis. ROC and survival analyses indicated that FeSig had good diagnostic and prognostic value. Further analysis revealed that ferroptosis was associated with tumour immunity in ccRCC. Next, weighted gene co-expression network analysis was performed to identify the potential regulatory mechanisms. Combined with correlation and survival analysis, the TAZ/WNT10B axis was identified as a tumour immune-related regulatory pathway. In conclusion, these findings suggest that ferroptosis is correlated with tumour immunity. The TAZ/WNT10B axis may be a novel biomarker and therapeutic target for immunotherapy in ccRCC.